2021
DOI: 10.3390/ma14133727
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ TEM Annealing Observation of Helium Bubble Evolution in Pre-Irradiated FeCoNiCrTi0.2 Alloys

Abstract: The FeCoNiCrTi0.2 high-entropy alloys fabricated by vacuum arc melting method, and the annealed pristine material, are face centered cubic structures with coherent γ’ precipitation. Samples were irradiated with 50 keV He+ ions to a fluence of 2 × 1016 ions/cm2 at 723 K, and an in situ annealing experiment was carried out to monitor the evolution of helium bubbles during heating to 823 and 923 K. The pristine structure of FeCoNiCrTi0.2 samples and the evolution of helium bubbles during in situ annealing were bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…And typical iron can be measured by using cobalt radiation to prevent fluorescence. [32] Previous research conducted by our group revealed that FeCoNiCr alloy possesses a homogenous single-phase composition, [33] consequently we shall not reiterate those findings here. The TEM images as shown in Fig.…”
Section: Tem Characterizationmentioning
confidence: 61%
“…And typical iron can be measured by using cobalt radiation to prevent fluorescence. [32] Previous research conducted by our group revealed that FeCoNiCr alloy possesses a homogenous single-phase composition, [33] consequently we shall not reiterate those findings here. The TEM images as shown in Fig.…”
Section: Tem Characterizationmentioning
confidence: 61%